2013
DOI: 10.1080/10503307.2013.849016
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Outcome Questionnaire-45.2: The Norwegian version in an international context

Abstract: The means, clinical cut-offs, and the reliable change index vary across countries. However, the means of the OQ-45 for nonclinical samples correlate highly with external values of national well-being, indicating that the OQ-45 is a valid instrument internationally. The factor analyses in the present study do not confirm the hypothesized factor structure of the OQ-45, but are similar to the results internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
0
18
0
6
Order By: Relevance
“…Each item is scored on a range from 0 to 4, giving a total score from 0 to 180 (lower is better), with a clinical cutoff at 64. The OQ‐45 shows satisfactory psychometric properties (Amble et al, ). Cronbach's alpha was in this sample .96 at the start of therapy, and .96 at the end of therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Each item is scored on a range from 0 to 4, giving a total score from 0 to 180 (lower is better), with a clinical cutoff at 64. The OQ‐45 shows satisfactory psychometric properties (Amble et al, ). Cronbach's alpha was in this sample .96 at the start of therapy, and .96 at the end of therapy.…”
Section: Methodsmentioning
confidence: 99%
“…The Norwegian version of the OQ-45 used in this study has been shown to have adequate test-retest reliability and internal stability (r = .85 and α = .93, respectively) and validity with other international instruments. The clinical cutoff score for the Norwegian version is 62 and the Reliable Change Index is 16 (Amble et al, 2014). …”
Section: Instrument and Fb Systemmentioning
confidence: 99%
“…Thus, the substantial misclassification cannot be explained by a lack of mental illness but instead by limitations, either of the measures used in assessing psychopathology or of the methodology used in assessing caseness. Analyses based on outpatients have reported sensitivity of above 90% for the OQ total scale [ 52 ] as well as the GSI scale [ 46 ]. Sensitivity values of at least 80% based on inpatient data were reported by Moessner et al [ 53 ] for both global scales using data from inpatients with an F3, F4, F5, or F6 diagnosis and by Timman et al [ 54 ] for the OQ Total Score using an inpatient sample with personality disorders.…”
Section: Discussionmentioning
confidence: 99%